El Instrumental de Pesca en el Fretum Gaditanum (siglos V A. C. - VI D. C. ) Análisis Tipo-Cronológico y Comparativa Atlántico-mediterránea. - Vargas Girón, José Manuel (Archaeopress, 2020)
The study of fishing tackle is an innovative area of research which is improving our understanding of one of the most important past economic activities: fishing. This book analyses fishing tackle in the region known as Fretum Gaditanum (the Strait of Gibraltar), where over a thousand pieces of evidence have been inventoried.